The Relationship of Anxiety Emotional Intelligence and Concentration of Thinking to the Decision-Making Ability of Football Referees - M Alif Hamzah (Universitas Riau, 2024)
This study aims to determine the relationship between anxiety, emotional intelligence, and concentration of thinking with the decision making of football referees in Aceh Besar Regency. This study adopts a quantitative approach with a correlational descriptive method. The population that was the focus of this study was football referees in Aceh Besar Regency, which amounted to 55 people. The sampling technique used is Total Sampling. The results of the study 1) The Relationship between Anxiety About Football Referee Decision Making with Fcount Results 24.522> Ftable 4.02, 2) The Relationship between Emotional Intelligence on Football Referee Decision Making with Fcount Results 17.977 > Ftable 4.02, 3) The Relationship between Thinking Concentration on Football Referee Decision Making with Fcount Results 15.858 > Ftable 4.02, 4) The Relationship between Anxiety, Emotional Intelligence and Thinking Concentration on Decision Making Football Referee with Fcount results 28.356 > Ftable 2.79. The conclusion is that there is a significant relationship between the level of anxiety and decision making of football referees, there is a significant relationship between the level of emotional intelligence and decision making of football referees, there is a significant relationship between the level of concentration of thinking and decision making of football referees, there is a significant relationship between the level of anxiety, emotional intelligence, and concentration of thinking with the decision making of football referees Aceh Regency Big.